2016
DOI: 10.1002/cbin.10634
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 inhibits angiotensin II‐induced podocyte autophagy via AMPK/mTOR/PI3K pathway

Abstract: Recent researches have reported the extensive pharmacological activities of Ginsenoside Rg1 including antioxidant, anti-inflammatory, and anticancer properties. Furthermore Rg1 was also shown to protect various kinds of cells from self-digestion by its anti-autophagy activity. In previous studies, angiotensin II (Ang II), a key mediator of renin-angiotensin system, has been demonstrated to contribute to the progression of renal injury including abnormal autophagy. However, whether Rg1 can relieve Ang II-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…Most recently, Rg2 was reported to exhibit neuronal and metabolic benefits through autophagy induction [36]. Interestingly, in a report it was shown that Rg1 inhibited angiotensin II-induced podocyte autophagy via the AMPK/mTOR/PI3K pathway [37]. However in another study, Rg1 was demonstrated to reduce aldosterone-induced autophagy via the AMPK/mTOR pathway in NRK-52E cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Rg2 was reported to exhibit neuronal and metabolic benefits through autophagy induction [36]. Interestingly, in a report it was shown that Rg1 inhibited angiotensin II-induced podocyte autophagy via the AMPK/mTOR/PI3K pathway [37]. However in another study, Rg1 was demonstrated to reduce aldosterone-induced autophagy via the AMPK/mTOR pathway in NRK-52E cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Convincing evidence showed that AMPK-mTOR pathway is important in regulating autophagy (25,47). Activation of AMPK is capable of inhibiting the phosphorylation of mTOR, and thus promotes cell autophagy (24,48). Autophagy is closely related to tumor metastasis, EMT, apoptosis and drug resistance (4951).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II (Ang II), a key mediator of the renin–angiotensin system, has been demonstrated to induce abnormal autophagy in podocytes, resulting in renal injury. Rg1 can both downregulate the activity of AMPK and GSK‐3β to suppress Ang II‐induced autophagy by activating mTOR signaling, as well as increase the activity of P70S6K, a downstream effector of the mTOR complex 1 (mTORC1), to block Ang II‐induced autophagy via a negative‐feedback loop by inhibiting PI3K . Similarly, Rg1 was also found to inhibit aldosterone‐induced autophagy and hypoxia/reperfusion‐induced autophagy, in which the suppression of AMPK and activation of mTOR were shown to be the primary underlying mechanisms.…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
“…The ginsenosides that serve as autophagy inducer include CK, Rg3, Rh2, Rg1, Rg2, and F2 . Meanwhile, the ginsenosides that can inhibit autophagy include Ro, Rg3, Rg1, and Rb1 (Fig. ).…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
See 1 more Smart Citation